Küresel Kent Söyleminin Kentsel Mekana Ve Mimarlığa Etkisi: İstanbul Örneği - Taşkın, Volkan (Fen Bilimleri Enstitüsü, 2016)
Küreselleşme günümüzde olan sosyal ve ekonomik gelişmeleri açıklamakta sık sık başvurulan bir terim haline gelmiştir. Bu terimle alakalı olarak ortaya çıkan küresel kent terimi de özellikle son zamanlarda kentlerde yaşananları anlatmak için başvurulan bir başka terimdir. Küreselleşme kılıfı altında sürdürülen neo-liberal ekonomik politikalar, İkinci Dünya Savaşı sonrasında dünya genelinde yaşanan hızlı kentleşmenin katalizörlerinden birisi olmuştur. Bu yeni kentleşme çağında, kentleşme hızı hem artmış hem de ağırlık merkezini Batı’dan Doğu’ya ve Güney’e kaydırmıştır. Bahsi geçen bu hızlı kentleşme, kamu fonlarının yetersizliği ile birleşince, kentleri yönetenleri yeni para kaynakları aramaya itmiştir. Aynı dönemde, ülkelerin katı finansal politikaları da gevşemeye başlamış, bunu takiben yıllarca batının finansal araçlarında biriken sermaye, mobil bir hale gelerek bu yeni kentleşen alanları, yüksek karlı iş alanları (hizmet ve emlak başta olmak üzere) için uygun yerler olarak belirlemiştir. Büyüyen kentlerin parasal kaynaklara olan ihtiyacı bu küreselleşen kapitalden kentlerine pay çıkarmak isteyen yerel elitlerin elinde bir mücadele alanı haline gelmiş, kentsel mekân da bu mücadelenin ön cephesine dönüşmüştür. Araştırmanın temeli günümüzde artarak devam eden bu küresel durum üzerine kurulmuştur. Merkezine aldığı soru, küreselleşmenin ve küresel kent söylemlerinin kentsel mekân ve mimarlık üzerinde nasıl sonuçları olduğudur. Küreselleşme akademik bir kavram olarak ele alınırken zaman ve mekân üzerinden düşünülerek tartışılmaktadır. Öte yandan, küreselleşmenin somut olarak mekâna ve kente olan etkileri çoğu zaman ekonomik ve sosyal alanlarda değerlendirilmektedir. Bu araştırma, küreselleşmenin bu etkilerini mimarlık ve mekân ekseninde değerlendirerek tartışmayı küreselleşmeyi tanımlayan soyut mekân-zaman ilişkisinden somut kentsel mekâna taşımayı amaçlamaktadır. Bu bağlamda araştırmanın ekseni iki ana grupta toplanan dört katmana bölünmüş durumdadır. Katmanlar daha soyut ve genel tartışmalardan başlayarak, kente, kentsel mekâna ve en sonunda bina ölçeğine kadar inmektedir. İki ana grupsa, bir tarafta küreselleşme ve küresel kent söylemi etrafındaki genel tartışmaya odaklanırken, diğer tarafta ise bu tartışmadan çıkan sonuçlar İstanbul özelinde incelenmekte, özgün bir örnek olarak İstanbul’un bu küresel kent söyleminde nerede yer aldığının araştırması yapılmaktadır. İlk katmanda kavramsal çerçeveyi belirlemesi için küreselleşme ve küresel kent kavramları tartışılmıştır. Saçaklı bir kavram olarak tanımlanan küreselleşmenin, bu bağlamda farklı, hatta birbirleriyle çelişen tanımlamalarına değinilmiştir. Kavramların yaşadığı anlam kaymaları da göz önüne alınarak, kavramsal çerçevenin ikinci merkezini oluşturan küresel kent kavramı, bütün hipotezleri ile ele alınmıştır. Sonrasında küresel kent hipotezine getirilen eleştiriler tartışılmış, teorik boşluk ve çelişkilerden dolayı, küresel kent hipotezlerinin içi boşaltılarak nasıl politik söyleme dönüştürüldüğü ele alınmıştır. İkinci katman ise küresel kent söyleminin mekânsal yansımalarının araştırılması hakkındadır. Küresel kent bir söylem olsa da, aynı zamanda kenti yönetenlerin elinde mekânları etkileyen bir politik araca dönüşmektedir. Küresel kent söylemine göre şekillenen kentsel mekânlar, ekonomik merkez, kamusal alan, konut dokusu ve mimari tipolojiler ekseninde incelenmektedir. Ekonomik merkez olarak, kentlerin yeni merkezleri olduğu iddia edilen uluslararası finans ve iş merkezleri incelenmektedir. Finans merkezlerinin mekânsal yapısını anlamak için iki yönlü bir okuma yapılmaktadır: bir taraftan finans sektörünün gelişimi ve mekânsal talepleri incelenirken, bir yandan da iş bölgelerinin kurucu ögesi olan ofis yapıları küreselleşme kapitalizm ekseninde ele alınmaktadır. Kamusal alan, özel sektör – kamu ekseninde tartışılmakta; küreselleşen kentlerde kamusal alanın yapımında özel sektörün üstlendiği yeni rollere değinilmektedir. Konut başlığı altında ise, küreselleşme sonucu kent içinde artan kutuplaşma, konut yerleşimleri ve kent makroformu içindeki yerleri / hareketleri üzerinden ele alınmaktadır. Son olarak, küreselleşen kentlerde, kentsel dokuyu heterojenleştiren karma-kullanımlı (melez) yapılar ve kentlere marka değeri kattığı iddia edilen ikonik yapılar üzerinden küresel kentlerin bina tipolojileri tartışılmaktadır. Böylece bu iki katmanda, küreselleşme ve küresel kent kavramları tartışılmış ve devamında küresel kent söyleminin fiziksel çevrede nasıl sonuçları olduğuna değinilmiştir. Araştırmanın ikinci büyük gövdesi ile İstanbul hakkındadır. İlk grupta ortaya çıkan tespitler ışığında, İstanbul küreselleşme ve küresel kent söylemi eksenlerinde ele alınmıştır. Önce, Tanzimat Dönemi’nden başlayarak, Osmanlı İstanbul’unun batılılaşma ekseninde yaşadığı ilk küreselleşme dönemi incelenmektedir. Daha sonra sırasıyla, ulus devletin kurulması ve 1980 sonrası liberal ekonomiye geçişle yaşanan ikinci küreselleşme dönemi ele alınmaktadır. 1980 sonrası dönem, o zamanki iktidar odaklarının ortaya koyduğu “Dünya Kenti / Küresel Kent İstanbul” söylemi ekseninde ele alınmaktadır. 24 Ocak kararları ile liberal ekonomiye geçen Türkiye ve İstanbul’daki yeni politik ve ekonomik durumun, küreselleşme ekseninde izi sürülmektedir. Böylece, İstanbul’un son 180 yıllık tarihi küreselleşme ekseninde incelenmiştir. İkinci bölümde, bu tarihsel sürecin mekânsal sonuçları ele alınmaktadır. 1980’e kadar olan süreç sadece tarihsel bir okuma olarak ele alınmaktadır. 1980 sonrası dönem ise, hem tarihsel olarak hem de üçüncü bölümde kategorize hale getirilen mekânsal sonuçlar ışığında ele alınmaktadır. Buna ek olarak, 1980 sonrası ortaya çıkan yeni döneme özgü durumlar da İstanbul’un kendi küreselleşme söylemini tamamlayıcı niteliktedir. Burada, iktidar ve sermaye grupları arasındaki anlaşma ve çatışmaların planlama ve mimarlık boyutunda nasıl etkileri olduğuna odaklanılmıştır. Buraya kadar, kent genelinde küresel kent ve İstanbul ilişkisine odaklanan araştırma; küreselleşme ve küresel kent söyleminin mekânsal etkilerine daha yakın ölçekten bakmak amacıyla, Levent-Maslak aksına odaklanmıştır. Burada yapılan çalışmalar sonucu ortaya çıkan üç temel arketip, üç bina üzerinden incelenmiştir: Levent Loft (üst-gelir için konut odaklı proje), Kanyon (karma kullanım projesi) ve Maslak No:1 (Çok Katlı Ofis Yapısı). Bu üç proje, mimari özellikleri, binanın kendisini çevreleyen söylem ve bu söylemin İstanbul’un küresel kent söylemi ile kurduğu ilişki bağlamında ele alınmıştır. Araştırmanın sonunda ise, bu iki ana araştırma alanından (genel ve lokal) elde edilen bulgular ve tespitler ışığında, küresel kent söylemi, kentsel mekan ve mimarlık ilişkisinin sonuçları üç ana eksende (kent, mimarlık ve mimar) değerlendirilmiştir. Bu değerlendirmeler ışığında, metnin de başında bahsedilen yeni kent gerçekliğinin ortaya koyacağı yeni kavramsal çerçevenin neler olabileceği hakkında çeşitli çıkarımlar yapılmıştır.

Globalization is a phenomenon that is widely used to explain the current social and economic conditions. Related to globalization, global cities a rather new term coined by researchers to understand the impact of globalism in cities. In contemporary urban discourse, the term global city gained widely acceptance as a term to comprehend the ongoing transformations in certain parts of the globe. Neo-liberal economic policies coming in the form of globalism and global cities concepts, has been a major catalyst for the rapid urbanization of the world since the aftermath of The Second World War. After 1950’s, the urbanization rate both accelerated and shifted towards the East and the South, creating a new breed of urban sprawls that are ripe for global finance. The rapid urbanization and lacking of sufficient public funds to challenge this growth, the governing elite of these new mega cities looked upon global finance as a potential savior. As the deregulation of the finance sector increased over the last three decades, the money piled up in financial instruments of the Western World became more mobile, thus finance sector looked for high-profit opportunities in these newly created urban fabrics. The foundation of this research launches off from this contemporary economic realm. It aims to find how the urban space and the architecture that defines this urban space is affected by the ongoing discourse of the global city. The term globalization itself is always explained by space and time, thus thinking about globalization is thinking about space itself. In addition to that, the term global city became a de facto condition to summarize the ongoing effects of neo-liberalism on urban space. This research aims to shift the focus on globalization from economic and social scales to urban and spatial scale. The methodology of the research creates four layers grouped into two main bodies. The layers start from general, meaning conceptual discourses and gradually focuses on space, finishing in the case study city and finally case study area. The two bodies are separated by general and local focuses. The first body takes the topic on a more general level, focusing on globalism, global cities and the physical environment of the global cities. The second body takes these discussions and applies to Istanbul where globalism and neo-liberal economy gained a fast track since 1980. The first part of first body aims to discuss the fuzziness of the definition of globalism and how it effects the terms usage in different aspects of life including economic, political and cultural layers. Globalism is a term that cannot be confined into certain words and definitions, thus making the term used in many different ways and forms sometimes contradicting each other. Global city (World city), derived from globalism itself, has been an active term for debate since 1960s. However based on a fuzzy concept like globalism and having its own theoretic flaws, the global city hypothesis alone fails to comprehend the effects of globalism on urban space. Despite these disadvantages, the global elite and its local counterparts used global city concept as a political and economic discourse to implement neo-liberal economic policies on urban centers of the World. Thus, the global city hypothesis which is confined into academic debates transformed into the global city discourse which is the pivotal point of this research. The second part of the first body aims to correlate the effects of globalization on urban space. Main elements of the urban fabric are analyzed in separate cases. The emergence of international finances centers in the city downtowns and business districts is the first case. This case is focused on how modern finance collaborated with modernist office space and together they warped the business life and its spatial outcomes. The second case focuses on the prime element of any urban fabric: housing. This case focuses on how the increasing polarization between global elites, the lucky minority who reaps the benefits of globalism, and the rest, as these global elites transform both the core and the outskirts of the city into high-income neighborhoods, leaving the urban poor out of the picture. The third major case focuses on public space, to be specific on how public space is created in global cities. In the expanding global cities limited public funds are focused on transportation and infrastructure, leaving urban space without the patronage of public administration. This power vacuum is filled by interventions of the private sector, in terms of Privately Owned Public Spaces (POPS) and similar methods. The final case focuses on the architecture of this new urban space of the global cities. Hybridization and iconic buildings are the focuses of this chapter. The second body of research then focuses on Istanbul, as a case study to understand how this concept of global city and its spatial outcomes occur in İstanbul’s urban conditions. Here, the general conditions of the discourse meets with the local and sometimes unique conditions of the city, thus creating a sub-discourse within the main global city discourse. To understand the effects of global city, first Istanbul is evaluated on its relationship with globalism. Based on a historical context, Istanbul has always been a world city, regarding its prime importance for Roman, East Roman and Ottoman Empires. However, speaking in terms of contemporary globalism, Istanbul’s globalization story dates back to Ottoman Empire’s Westernization efforts beginning officially in 1839 by the Edict of Gülhane. After that, the city opens itself to modern urbanism, finance and local administrative bodies. Istanbul’s globalization history is cut down with emergence of the Turkish Republic and its mercantilist economic policies. However, after 1980 Turkey enters into liberal economic system overnight and ruling elite decides to promote Istanbul as a global city to attract foreign capital. Thus begins the second part of Istanbul’s emergence as a global city.Starting from 1980 reaching up present day, is the main timeline of the research. Unlike the 19th century’s global theater, the conditions that turned Istanbul to a global city are a result of a deliberate discourse built by the governing elites and funded by Turkey’s largest capital groups.Istanbul first promoted as a world city and local contender for replacing the war-ridden Beirut –once the finance capital of the region. Then the governing elite aimed for higher goals and İstanbul found itself competing with cities like Hong Kong, Dubai, London and New York. Though this dream of a global city is not embraced by other major political moves at first, the increasing demand for capital to accommodate the needs of an ever-growing city like İstanbul forced every major political player to accept the main discourse and forge their own unique global city discourse that aims to excel gaining maximum financial support. Istanbul is transformed from an industrial major port city to a haven of real estate speculation and consumption. The global city discourse changed major parts of the urban fabric, with this change came a new culture of consumption and lifestyle, and defined the contemporary architectural trends in the city. Therefore, the research goes in hand-to-hand with the timeline staring from 1980 to present day and examines the situation on the different layers. The first layer focuses on how this discourse is fabricated and the second layer focuses on how this fabricated discourse affected the urban space and architecture. Then the research zooms into places where effects of globalization are felt most. The financial center of Levent and Maslak is chosen as the prime case study area to analyze the situation on a more close-up level. Maslak and Levent district is once-an-industrial-site turned into international finance and business center after 1980s. Since then, the place and its high-rise silhouette became the symbol of the new economic regime in Istanbul and Turkey. The buildings designed and built in this district are concrete products of the global city discourse. Thus, to understand the architecture of this discourse, buildings in the district are analyzed in terms of architecture and the discourse that surrounds this architecture. Built mostly after 1990’s, these buildings are categorized into three major archetypes. In the research, one building represents each archetype: Levent Loft for the high-income condominium type, Kanyon for the mixed-use type and finally Maslak No: 1 is for the high-rise office building type. Each building is evaluated in three categories; first its architecture is presented, then the discourse that surrounds this building is evaluated. The discourse is created by the layers of discourse created by the architect, the client, and the people who use the building, media and social media. In the third stance, this discourse is discussed via its affiliation with the Istanbul’s global city discourse. In the final chapter, the data gathered from Istanbul and Maslak case studies are evaluated with the global city phenomenon in general and the results of the research are debated in terms of how to improve spatial conditions in the so-called global cities without alienating its inhabitants. Here, in the conclusion, the global city discourse is discussed on three different levels; urban space, the practice of architecture that creates the urban space and the architect as the professional behind the practice that defines the urban space. Finally, the remarks coming from these discussions are speculated upon how to improve the current theoretical framework that fails to understand the rapid and ongoing urbanization of the World, which would need far deeper concepts and terms than the discourses surrounding this reality, in order to properly accommodate the needs of this new urban realm.
The Effects Of The Global City Discourse On Urban Space And Architecture
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2016
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2016
Keywords: Küreselleşme; Küresel Kentler; Küresel Üretim Ağları; Modern Mimari; Globalization; Global Cities; Global Production Networks; Modern Architecture